2015
DOI: 10.5812/ircmj.28615
|View full text |Cite
|
Sign up to set email alerts
|

Better Hemodynamic Profile of Laryngeal Mask Airway Insertion Compared to Laryngoscopy and Tracheal Intubation

Abstract: Background:Laryngoscopy and tracheal intubation can cause serious cardiovascular responses in patients such as hypertension, tachycardia, and arrhythmias. Alternative airway maintenance techniques may attenuate these hemodynamic stress responses.Objectives:This study aimed to compare the immediate hemodynamic effects of the insertion of laryngeal mask airway supreme (LMA-S) and classic (LMA-C) with laryngoscopy and Endotracheal Intubation (ETT).Patients and Methods:This study was a prospective, double-blind, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
2
37
1
1
Order By: Relevance
“…2,3 Various therapeutic medications and methods have been employed to reduce or suppress cardiovascular responses caused by endotracheal intubation, 4 including local anesthesia, 5 intravenous lidocaine, 6 drugs affecting adrenergic receptors (eg, b-adrenoceptor antagonists, 7 a 1 -and a 2 -adrenocepter agonists 8 ), vasoactive agents (eg, glyceryl trinitrate, 9 calcium channel blockers, 10 sodium nitroprusside 11 ), and a laryngeal mask. 12 However, the optimal medicine or method to avoid stress responses in these patients has not been unequivocally established. 13 Pregabalin is a new generation of antiepileptic drug that interacts with the a 2 -d subunit of voltagedependent calcium channels in the CNS and inhibits neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Various therapeutic medications and methods have been employed to reduce or suppress cardiovascular responses caused by endotracheal intubation, 4 including local anesthesia, 5 intravenous lidocaine, 6 drugs affecting adrenergic receptors (eg, b-adrenoceptor antagonists, 7 a 1 -and a 2 -adrenocepter agonists 8 ), vasoactive agents (eg, glyceryl trinitrate, 9 calcium channel blockers, 10 sodium nitroprusside 11 ), and a laryngeal mask. 12 However, the optimal medicine or method to avoid stress responses in these patients has not been unequivocally established. 13 Pregabalin is a new generation of antiepileptic drug that interacts with the a 2 -d subunit of voltagedependent calcium channels in the CNS and inhibits neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Arı et al reported no significant difference in the amount of blood on LMA and I-GEL after removal from the airway [31], while Polat et al, did not report a significant difference in the responses to patients regarding pain after 24 h of use of the equipment [26]. In a study by Jarineshin et al there were no significant differences in hemodynamic variables (such as pulse or systolic and diastolic pressures) when comparing LMA and LMA-S devices with endotracheal intubation [38]. Utilization of LMA-S was reported by Van Esch and Kömür et al to result in the smallest number of airway complications [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…When AFOI is effectuated without sedation, it is commonly related to patient discomfort and severe hemodynamic responses, inducing catecholamine release by sympathetic sti-mulation, sympathetic stimulation, which may result in increased heart rate and blood pressure, arrhythmia, and cause myocardial ischemia and infarction in patients with risk factors, such as hypertension and ischemic heart disease [6,7]. The sedation may alleviate the awake intubation, but it requires conscientious administration and continuous monitoring as it can lead to airway obstruction and hypoxemia, while inadequate sedation could lead to discomfort, anxiety and excessive sympathetic discharge.…”
Section: Introductionmentioning
confidence: 99%